Features of displays of sense of humor as adaptive mechanism: coping strategy or a defense mechanism? - Olexandra Mitrova (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
This article discusses the sense of humor as a mechanism of psychological overcoming and its join with the social and psychological adapta- tion as a measure of the success of its application; it systemizes scientific developments in the field of humor and coping strategies and provides an overview of studies that investigates a sense of humor as coping mechanism. It also devides the concepts of coping-mechanisms and psycho- logical defenses of personality, which are two different types of reaction on stressing situations. The article presents the results of empirical research organized and held by the author, which examines features of humor because of the peculiarities of application of coping strategies, defense mechanisms and the level of socio-psychological adaptation of personality.